Troponin T and Heart Type Fatty Acid Binding Protein (h-Fabp) as Biomarkers in Patients Presenting with Chest Pain - Reddy, Lakshmi Lavanya (Indian J Clin Biochem, 2015)
Acute coronary syndrome (ACS) is a term for a range of clinical signs and symptoms suggestive of myocardial ischemia. It results in functional and structural changes and ultimately releasing protein from injured cardiomyocytes. These cardiac markers play a major role in diagnosis and prognosis of ACS. This study aims to assess the efficacy of heart type fatty acid binding protein (h-FABP) as a marker for ACS along with the routinely used hs-TropT. In our observational study, plasma h-FABP (cut-off 6.32 ng/ml) and routinely done hs-Trop T (cutoff 0.1 and 0.014 ng/ml) were estimated by immunometric laboratory assays in 88 patients with acute chest pain. Based on the clinical and laboratory test findings the patients were grouped into ACS (n = 41) and non-ACS (n = 47). The diagnostic sensitivity, specificity, NPV, PPV and ROC curve at 95 % CI were determined. Sensitivity of hs-TropT (0.1 ng/ml), hs-TropT (0.014 ng/ml) and h-FABP were 53, 86 and 78 % respectively and specificity for the same were 98, 73 and 70 % respectively. Sensitivity, specificity and NPV calculated for a cut-off combination of hs-TropT 0.014 ng/ml and h-FABP was 100, 51 and 100 % respectively. These results were substantiated by ROC analysis. Measurement of plasma h-FABP and hs-TropT together on admission appears to be more precise predictor of ACS rather than either hs-Trop T or h-FABP.